SANTORY: SANTORini’s Seafloor Volcanic ObservatorY - Nomikou, Paraskevi; Polymenakou, Paraskevi N.; Rizzo, Andrea Luca; Petersen, Sven; Hannington, Mark; Kilias, Stephanos Pantelis; Papanikolaou, Dimitris; Escartin, Javier; Karantzalos, Konstantinos; Mertzimekis, Theodoros J.; Antoniou, Varvara; Krokos, Mel; et al. (Frontiers in Marine Science, 2022)
Submarine hydrothermal systems along active volcanic ridges and arcs are highly dynamic, responding to both oceanographic (e.g., currents, tides) and deep-seated geological forcing (e.g., magma eruption, seismicity, hydrothermalism, and crustal deformation, etc.). In particular, volcanic and hydrothermal activity may also pose profoundly negative societal impacts (tsunamis, the release of climate-relevant gases and toxic metal(loid)s). These risks are particularly significant in shallow (<1000m) coastal environments, as demonstrated by the January 2022 submarine paroxysmal eruption by the Hunga Tonga-Hunga Ha’apai Volcano that destroyed part of the island, and the October 2011 submarine eruption of El Hierro (Canary Islands) that caused vigorous upwelling, floating lava bombs, and natural seawater acidification. Volcanic hazards may be posed by the Kolumbo submarine volcano, which is part of the subduction-related Hellenic Volcanic Arc at the intersection between the Eurasian and African tectonic plates. There, the Kolumbo submarine volcano, 7 km NE of Santorini and part of Santorini's volcanic complex, hosts an active hydrothermal vent field (HVF) on its crater floor ( 500m b.s.l.), which degasses boiling CO2–dominated fluids at high temperatures ( 265°C) with a clear mantle signature. Kolumbo's HVF hosts actively forming seafloor massive sulfide deposits with high contents of potentially toxic, volatile metal(loid)s (As, Sb, Pb Ag, Hg, and Tl). The proximity to highly populated/tourist areas at Santorini poses significant risks. However, we have limited knowledge of the potential impacts of this type of magmatic and hydrothermal activity, including those from magmatic gases and seismicity. To better evaluate such risks the activity of the submarine system must be continuously monitored with multidisciplinary and instrumentation as part of an in-situ observatory supported by discrete sampling and measurements. This paper is a design study that describes a new long-term seafloor observatory that will be installed within the Kolumbo volcano, including cutting-edge and innovative marine-technology that integrates hyperspectral imaging, temperature sensors, a radiation spectrometer, fluid/gas samplers, and pressure gauges. These instruments will be integrated into a hazard monitoring platform aimed at identifying the precursors of potentially disastrous explosive volcanic eruptions, earthquakes, landslides of the hydrothermally weakened volcanic edifice and the release of potentially toxic elements into the water column.